[Comment] Long term outcomes of D2 vs. D3 lymph node dissection for cT2N0M0 colorectal cancer: a multi-institutional retrospective analysis - Li Shaotang (结直肠肛门外科)
[Background] According to Japanese guidelines, D2 or D3 lymph node dissection (LND) is indicated for cT2N0M0 colorectal cancer (CRC). In this study, we retrospectively compared the long-term outcomes between D2 and D3 LND among patients with cT2N0M0 CRC. [Methods] Our sample included 515 patients from the Japanese Study Group for Postoperative Follow-Up of Colorectal Cancer database, who underwent surgical resection for cT2N0M0 CRC between January 2009 and December 2012, 195 (37.9%) of whom underwent D2 LND and 320 (62.1%) D3 LND. The D2 and D3 groups were retrospectively compared in terms of long-term outcomes including overall survival (OS) and relapse-free survival (RFS). The prognostic factors for these outcomes were also evaluated. [Results] The D2 group had significantly older patients and higher proportion of men than the D3 group. The rates of OS (5-year OS; 94.8% in the D3 group vs. 93.4% in the D2 group, p = 0.38) and RFS (5-year RFS; 89.3% in the D3 group vs. 89.1% in the D2 group, p = 0.91) were comparable for both groups. On multivariate analysis, age ≥ 80 years was significantly associated with poor OS. The extent of LND was not associated with either OS or RFS. Long-term outcomes were similar between the two groups, independent of tumor location. [Conclusion] The long-term outcomes did not differ between the D2 and D3 groups and the extent of LND was not associated with prognosis for cT2N0M0 CRC. Therefore, D2 LND may be sufficient for cT2N0N0 CRC treatment.